Deployment of a Dense Seismic Network on La Palma Island (2023-2024) for High-Resolution Imaging of the Velocity Structure Using Passive Seismic Methods - Javier Tortosa; Javier Almendros; Enrique Carmona; José Benito Martín; Janire Prudencio; Joan Antoni Parera-Portell; Rafael Abella; Carlos Araque-Pérez; José Morales; Pablo Rey-Devesa; Benjamin Heit; Xiaohui Yuan; et al. (Surveys in Geophysics, 2026)
We present the IMAGMASEIS project, a large-N seismic experiment carried out on La Palma (Canary Islands, Spain) between 2023 and 2024, aimed at high-resolution imaging of the crustal and upper mantle structure using passive seismic methods. The project involved the deployment of 235 temporary broadband and short-period seismic stations, supplementing 21 permanent stations, thus creating the densest seismic network ever installed on the island. The main goal is to characterise the magmatic plumbing system beneath Cumbre Vieja volcano, identify magma accumulation zones, and investigate structural changes related to the 2021 Tajogaite eruption. We describe the experimental design, network configuration, instrumentation, deployment strategies, and challenges encountered, including difficult terrain and logistical constraints. Preliminary results demonstrate the potential of the dataset for ambient noise tomography, receiver function analysis, and local earthquake studies. IMAGMASEIS provides a valuable resource for understanding volcanic and tectonic processes in oceanic island settings and serves as a model for cost-effective, high-density seismic deployments in similar environments.

Structure and seismogenic activity of the broken foreland to the south of the Chilean-Pampean flat subduction zone: The San Rafael Block - Julián Olivar; Silvina Nacif; Mario Giménez; Benjamin Heit; Lucas Fennell; Andrés Folguera (Journal of South American Earth Sciences, 2023)